Effects of Nitrogen Fertilization and Nitrogen Fixing Endophytic Bacteria Supplementation on Soil Fertility, N Uptake, Growth, and Yield of Sesame (Sesamum indicum L.) Cultivated on Alluvial Soil in Dykes - Le Vinh Thuc; Tran Ngoc Huu; Trinh Minh Ngoc; Nguyen Hong Hue; Le Thanh Quang; Do Thi Xuan; Tran Chi Nhan; Ly Ngoc Thanh Xuan; Le Thi My Thu; Isao Akagi; Jun-Ichi Sakagami; Nguyen Quoc Khuong (Applied and Environmental Soil Science)
The aim of this study was to determine the proper combination of nitrogen (N) fertilizer level and nitrogen fixing endophytic bacteria (NFEB) supplementation for the maximum grain yield of sesame cultivated in alluvial soil in dykes. The experiment followed a completely randomized block design with two factors. The first one was the levels of N fertilizer used, including 0, 50, 75, and 100% N of recommended fertilizer formula (RFF), and the other consisted of no bacteria applied, an individual strain of Enterobacter cloacae ASD-48 or E. cloacae ASD-21 applied, and their mixture, with 5 replicates. The results revealed that fertilizing with 100% N of RFF led to an enhancement of the plant height (16.8 cm), the chlorophyll a and b and their total content (6.45, 1.86, and 8.30 μg mL−1), the number of capsules per plant (7.22 capsules plant−1), the total N uptake (126.5 mg N pot−1), and the grain yield (9.08 g pot−1), in comparison to no N fertilizer applied. Supplementation of two NFRB strains enhanced the soilconcentrations of NH4+ and NO3−, the total N uptake, and the grain yield. The treatment fertilized with 75% N of RFF plus an individual NFEB strain or their bacterial mixture had equivalent total N uptake to that the treatment fertilized with 100% N of RFF had, 120.8–125.5 mg N pot−1 compared to 124.4 mg N pot−1. Regarding the sesame yield, with a reduction by 25–50% N of RFF plus ASD-48 and ASD-21, either individually or in mixture, it increased by 2.39–8.56%, compared to that in the treatment fertilized with 100% N of RFF.